Exploring visual representations to support data re‐use for interdisciplinary science. Issue 1 (1st February 2019) - Wiggins, Andrea; Young, Alyson; Kenney, Melissa A.
ABSTRACT: Data discovery and re‐use remain challenging, particularly for interdisciplinary research, but visual representations of data may have potential to better support these tasks than text‐only metadata records. Our multi‐stage exploratory study used think‐aloud and intercept interviews to evaluate how scientists across multiple disciplines interpret the content and evaluate the credibility of climate indicators designed for general audiences as a way to understand the potential of visual representations for supporting interdisciplinary research. Climate indicators provided a convenient alternate representation for describing a data set, featuring a visualization of the data along with vernacular textual description. Our contributions include (i) findings on the preferences of scientists from multiple disciplines for establishing the credibility and assessing the content of data for re‐use, (ii) the unexpected observation that a minimal set of core metadata was considered adequate by researchers examining data from outside of their specialties, and (iii) discussion of the implications for the design of data discovery interfaces and future research to support data discovery and re‐use by increasingly diverse scientific data consumers.